Full Cost Accounting for Renewable Natural Gas Produced from High Concentration Organic Wastewater - Shuyun Li; Siqi Wang; Fang Wang; Zhiwei Li; Raymond R. Tan; Xiaoping Jia (Chemical Engineering Transactions)
High-concentration organic wastewater (HCOW) has great potential in the production of renewable natural gas. However, in the conversion process from HCOW to biofuel, many influencing factors are not yet included in the cost accounting. To address this issue, this work introduces the method of full cost accounting (FCA). This method first identifies potential environmental and social factors that may arise during wastewater treatment, and uses environmental impact assessment and monetary evaluation to each influencing factor. Then, the monetary evaluation shows that the unit cost of renewable natural gas is 3.71 CNY/m3, which is 1.57 times of the economic cost that do not take into account environmental and social externalities. It provides a monetary indicator to enable calculating the hidden costs of unsustainable practices for sustainability assessment, which can comprehensively consider economic, environmental and social aspects.